How do we get people into contact? Predictors of intergroup contact and drivers of contact seeking. (31st October 2020) - Kauff, Mathias; Beneda, Marta; Paolini, Stefania; Bilewicz, Michał; Kotzur, Patrick; O'Donnell, Alexander W.; Stevenson, Clifford; Wagner, Ulrich; Christ, Oliver
Abstract: Compared to the impressive amount of research on consequences of intergroup contact, relatively little work has been devoted to predictors of intergroup contact. Although opportunities for intergroup contact are constantly growing in modern diverse societies, these contact opportunities are not necessarily exploited. In the present review article, we describe current research on predictors of intergroup contact and drivers of contact seeking on a micro‐, meso‐, and macro‐level. We provide an overview of predictors, while focusing on recent research that is especially relevant for designing interventions and planning social policies aiming at increasing contact between different groups in varied societies. On the micro‐level, we discuss relational self‐expansion motives and confidence in contact as predictors of intergroup contact. On the meso‐level, we focus on the role of intragroup processes and historical intergroup conflicts in facilitating contact. On the macro‐level, we reflect on changing societal norms as a potential tool to increase the frequency intergroup contact. By focusing on the applied value of research findings, discussing diverse predictors, and applying a multilevel approach, we also address recent criticisms of the intergroup contact literature and demonstrate the generative nature of contemporary research in this area.